Carbon Nanodots: Dual‐Color‐Emitting Carbon Nanodots for Multicolor Bioimaging and Optogenetic Control of Ion Channels (Adv. Sci. 11/2017). Issue 11 (23rd November 2017) - Kim, Hyemin; Park, Yoonsang; Beack, Songeun; Han, Seulgi; Jung, Dooyup; Cha, Hyung Joon; Kwon, Woosung; Hahn, Sei Kwang
Abstract : Carbon nanodots (CNDs) have been widely investigated for theranostic applications including fluorescence imaging, photoacoustic imaging, photothermal therapy, and photodynamic therapy. In article number1700325, Sei Kwang Hahn, Woosung Kwon, and co‐workers develop dual‐color‐emitting CNDs uniquely designed by the electronic structure engineering for both futuristic multi‐color bioimaging and optogenetic control of ion channels.